Four-Step Entrepreneurial System Approach to Control Students Dropout from Secondary School in Indonesia and Supply Chain Performance - Winarti, Agus (International Journal of Supply Chain Management, 2019)
Student dropout is one of the crucial challenges at Indonesian secondary schools. Increase in dropout ratio has negative consequence towards supply chain performance (SCP). Various studies discussed the issue of student dropout and provided various solutions, however, it is still under discussion among the scholars and practitioners which requires a comprehensive framework. Hence, the objective of this study is twofold. This study primarily focused on two major areas, firstly; introduce various strategies to overcome the student dropout rate at secondary school, secondly; to consider the effect of student dropout ratio on SCP. For this purpose, a survey was carried out and data were collected from secondary school teachers in Indonesia. To carry out a survey, 500 questionnaires were distributed among the secondary school teachers. Results of the study highlighted that, four-step entrepreneurial system approach which is based on four major parts, namely; self-assessment, goal identification, planning and networking has significant role to decrease the student dropout ratio. Moreover, student dropout ratio has negative relationship with SCP. Additionally, entrepreneurial fun learning strengthens the relationship between four-step entrepreneurial system and student dropout ratio.